2006
DOI: 10.1007/s00330-005-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI findings in KIT-weak or KIT-negative atypical gastrointestinal stromal tumors

Abstract: The large majority of gastrointestinal stromal tumors (GIST) can be diagnosed on the basis of KIT immunoreactivity. However, some atypical tumors show weak or negative KIT expression. We studied the imaging characteristics of atypical GIST, reviewing CT and MRI findings in ten patients (eight men, two women; mean age 59 years) with atypical GIST. Radiological studies were evaluated by two radiologists by consensus and included CT and MR imaging in all patients. Pathological diagnoses were made from surgery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Previous studies (14, 18, 19) showed that typical GISTs appear as inhomogeneous enhancing extraluminal masses with either well‐defined or irregular borders on conventional MR sequences, such as T1W/T2W imaging and Gd‐DTPA‐enhanced images. A larger tumor size (≥ 5 cm) was found to have a predictive value with respect to high‐risk GISTs (11).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies (14, 18, 19) showed that typical GISTs appear as inhomogeneous enhancing extraluminal masses with either well‐defined or irregular borders on conventional MR sequences, such as T1W/T2W imaging and Gd‐DTPA‐enhanced images. A larger tumor size (≥ 5 cm) was found to have a predictive value with respect to high‐risk GISTs (11).…”
Section: Discussionmentioning
confidence: 98%
“…The primary tumour sites noted in our study are similar to other previous reports [ 18 , 19 ], with a similar demographic of presenting symptoms including gastrointestinal bleeding, abdominal pain and the presence of an abdominal mass [ 20 - 22 ]. CT and MRI are generally used for the preoperative imaging of GISTs [ 23 - 25 ]. However, there are no well-established, published guidelines to help surgeons determine the optimal manner in which to evaluate this intraabdominal, site-specific class of tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Neither CT nor MRI are currently able to differentiate between conventional GISTs and atypical (c-kit negative) GISTs [16]. Pathologists can be helped towards definitive diagnosis by other cellular markers (for example DOG-1 is positive in 40% of all kitnegative GISTs) or by molecular analysis of the KIT and PDGFRA genes.…”
Section: Accepted Manuscriptmentioning
confidence: 98%